2021
DOI: 10.3389/ffgc.2021.576908
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Natural Regeneration: Implications for Landscape Restoration in the Atlantic Forest, Brazil

Abstract: This study aimed to understand post-agricultural natural forest regeneration in the Southern Brazilian Atlantic Forest and its possible role as a cost-effective, passive approach to forest restoration. The study characterized vegetation structure, floristic composition, and the dynamics of secondary forest chronosequences. Data were collected from 159 plots (10 × 10 m each) across forest remnants in Santa Catarina State, covering forest ages that ranged from 2 to 60 years of regeneration after swidden agricult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 91 publications
(134 reference statements)
2
10
1
Order By: Relevance
“…The same pattern of succession was reported in other studies, in which different species, both pioneers and non-pioneer, initiate regeneration concurrently (van Breugel et al, 2007;Chazdon et al, 2007;Peña-Claros, 2003;Piotto et al, 2009). This pattern of richness and diversity of tree species found in our study is also reported to be common in secondary tropical forests (Siminski et al, 2021;Villa et al, 2018) given the high abundance of commercial species (Fig. 5a).…”
Section: Commercial Timber Species and Volume In Secondary Forestsupporting
confidence: 90%
See 2 more Smart Citations
“…The same pattern of succession was reported in other studies, in which different species, both pioneers and non-pioneer, initiate regeneration concurrently (van Breugel et al, 2007;Chazdon et al, 2007;Peña-Claros, 2003;Piotto et al, 2009). This pattern of richness and diversity of tree species found in our study is also reported to be common in secondary tropical forests (Siminski et al, 2021;Villa et al, 2018) given the high abundance of commercial species (Fig. 5a).…”
Section: Commercial Timber Species and Volume In Secondary Forestsupporting
confidence: 90%
“…While the need to restore degraded lands/forests is unquestioned, scaling up programs to achieve ambitious targets remains elusive because of several limiting factors, costs being an important one (Brancalion et al, 2016;Crouzeilles et al, 2017;Crouzeilles et al, 2020). Passive restoration through natural regeneration, after agriculture, has proved to be successful in some ways, suggesting economic efficiency as a factor that could incentivise management initiatives (César et al, 2020;Crouzeilles et al, 2020;Siminski et al, 2021). Nonetheless, even bringing the cost of investments to near zero may not even be sufficient to stimulate landowners to set aside parcels of their land for restoration, especially in the case of small farmers (Alarcon et al, 2017).…”
Section: Managing Secondary Forests For Timber Production and Ecosyst...mentioning
confidence: 99%
See 1 more Smart Citation
“…The structural parameters of EIV were higher than those reported by Siminski et al (2011;2021) for young secondary forests in the region. The difference could be explained by the presence of individuals of P. taeda with high DBH in the area assessed.…”
Section: Discussioncontrasting
confidence: 74%
“…Regardless of the species compositing, the regeneration of tree species in three habitats of Buah Hitam was successfully established during the natural process. The vertical structure relationship in the three habitats of Buah Hitam includes seedlings, trees, poles, and trees, where small individuals (seedlings and trees) were mostly larger than larger individuals (poles and trees) indicating as natural regeneration (Pamoengkas et al, 2019;Sales de Melo et al, 2019;Siminski et al, 2021) The individuals of Buah Hitam have a strong relationship with other tree species in which the ten species were mostly present along with Buah Hitam (Figure 5). The dendrogram was executed to see how many species had heterospecific associations forming the tree community.…”
Section: Discussionmentioning
confidence: 99%